2016
DOI: 10.1172/jci.insight.86419
|View full text |Cite
|
Sign up to set email alerts
|

Induced regulatory T cells in allograft tolerance via transient mixed chimerism

Abstract: Successful induction of allograft tolerance has been achieved in nonhuman primates (NHPs) and humans via induction of transient hematopoietic chimerism. Since allograft tolerance was achieved in these recipients without durable chimerism, peripheral mechanisms are postulated to play a major role. Here, we report our studies of T cell immunity in NHP recipients that achieved long-term tolerance versus those that rejected the allograft (AR). All kidney, heart, and lung transplant recipients underwent simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 41 publications
4
35
0
Order By: Relevance
“…Furthermore, the expansion of T regs in tolerant recipients was inhibited by blocking transforming growth factor (TGF)-b, which resulted in restoration of antidonor CD8 1 T cell responses. These observations suggest that specific loss of anti-donor CD8 1 T cell responses are maintained by donor-specific induced T regs [25]. We also found that T regs were enriched significantly in the kidney allograft of tolerant recipients.…”
Section: Preclinical Studiessupporting
confidence: 71%
“…Furthermore, the expansion of T regs in tolerant recipients was inhibited by blocking transforming growth factor (TGF)-b, which resulted in restoration of antidonor CD8 1 T cell responses. These observations suggest that specific loss of anti-donor CD8 1 T cell responses are maintained by donor-specific induced T regs [25]. We also found that T regs were enriched significantly in the kidney allograft of tolerant recipients.…”
Section: Preclinical Studiessupporting
confidence: 71%
“…Similarly, marked enrichment of FOXP3-expressing Tregs during the early post-transplant course has been observed following the non-myeloablative anti-CD2 mAb-based CKHCT protocol that leads to transient chimerism [31, 66]. Consistently, a recent study suggested donor-specific FOXP3+ Treg expansion in tolerant NHPs receiving a T cell depletion/costimulatory blockade-based transient chimerism CKHCT regimen [67]. Mouse models have decisively established a causal link between accumulations of donor-reactive FOXP3+ Tregs and transplant tolerance through a variety of experimental approaches, including targeted deletion of FOXP3-expressing Tregs, which disrupted well-established tolerance [68, 69].…”
Section: Ii) Tolerance Mechanisms Associated With Transient Mixed Chimentioning
confidence: 72%
“…58 Of note, recent data support the hypothesis that specific induction of Tregs by donor antigens plays a key role in tolerance induced by transient mixed chimerism in non-human primate recipients of kidney, lung and heart allografts (see later). 9 …”
Section: Immune Response To An Allograft: Discoveries With Clinical Imentioning
confidence: 99%